Deteksi Perkembangan Balita di PAUD Cahaya - Iis Pusparina; Filia Sofiani Ikasari; Dewi Irianti (PPNI UNIMMAN, 2023)
Growth and development are two different processes that cannot be separated and are equally important for children in the critical period of the first 0-5 years of life because they will have implications for the child's quality of life in the future. This phase is often referred to as the